Power Quality Improvements in Power Electronics-Based Equipment: A Insight into the Research Problem- Part I - Rajashekher Koyyeda,; T. C. Manjunath, (Journal of Power Electronics and Devices, 2020)
In this 1st part of the research paper, a brief review of the power quality improvements in power electronics-based equipment – an insight into the problem is presented in a nutshell. Here, how the power can be improved, i.e., the quality of the power which deteriorates due to the continuous switching on & off of the different types of loads is presented concisely. The paper serves as a shot in the arm for the researchers who want to work in the field of power electronics. The latter part of the matter presented in this paper is the work of another paper, i.e., the second part.